Professional financial computing using Excel and VBA - Tung, Humphrey K. K.; Lai, Donny C. F; Wong, Michael C. S. [ (Michael Chak Sham)] (Wiley Finance, 2010)
Often financial computing guidebooks provide only quick-and-dirty implementations of financial models, rarely related to real-world applications. Professional Financial Computing Using Excel and VBA provides reusable, flexible, real-world implementations of financial models